Can a Central Stitch over the Arantius' Nodules Provide a Solution for Pre-Operative Severe Native AI in LVAD Patients?. Issue 3 (March 2013) - De Praetere, Herbert; Jacobs, Steven; Rega, Filip; Droogne, Walter; Meyns, Bart
Purpose: To evaluate the evolution of aortic valve insufficiency (AI) after Park's central stitch in patients with severe, pre-operative, native aortic valve insufficiency. Methods: We retrospectively studied 71 continuous flow LVAD patients between January 2004 and December 2010. Four patients with AI≥3/4 were treated with a central stitch. An intensive review of the literature was performed to debate the use of the central stitch in this population. Results: The AI at baseline (AI = 2.75 ± 0.5) and AI at last measurement (AI = 0.75 ± 0.65) is statistically different after central stitch (p<0.05) with mean follow up of 198.25 (± 146.70) days. Total cross clamp-time during the placement of the stitch was 15.5 minutes (± 13.062). CVA was not diagnosed in our cohort. Conclusions: Park's central stitch can be successfully performed on patients with severe native AI (≥3/4) with good long-term results. Short ischemic time and simple application of the stitch are the biggest advantages. Due to the progression of AI in longstanding LVAD, the central stitch may be beneficial for LVAD in destination therapy. Since this is a small group of patients and also an early experience, more cases will be necessary to confirm these positive results.